Didymocarpus anningensis (Gesneriaceae), a new species from Yunnan, China - Cai, Lei; Cai, Jie; Shui, Yu-Min (Phytotaxa, 2016)
A new species of Gesneriaceae, Didymocarpus anningensis, is described and illustrated from Anning, Central Yunnan, China. The new species resembles D. purpureobracteatus and D. yunnanensis, but it can be easily distinguished by a combination of stem, leaf blade and leaf petiole indumentum characters, bract and calyx shape and number of staminodes.